PENGARUHÃ‚Â SARANAÃ‚Â DANÃ‚Â PRASARANAÃ‚Â BELAJARÃ‚Â TERHADAPÃ‚Â HASILÃ‚Â BELAJARÃ‚Â MATAÃ‚Â PELAJARANÃ‚Â ALATÃ‚Â UKURÃ‚Â Ã‚Â Ã‚Â - Eko, Budiarso; Suwahyo, -; SetiadiÃ‚Â , - (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2008)
Permasalahan Ã‚Â dalam Ã‚Â penelitian Ã‚Â ini Ã‚Â adalah Ã‚Â seberapa Ã‚Â besar Ã‚Â pengaruh Ã‚Â sarana Ã‚Â dan Ã‚Â prasarana Ã‚Â praktikÃ‚Â belajar Ã‚Â dengan Ã‚Â Ã‚Â hasil Ã‚Â belajar Ã‚Â mata Ã‚Â diklat Ã‚Â Ã‚Â alat Ã‚Â ukur, Ã‚Â dan Ã‚Â berapakah Ã‚Â besaran Ã‚Â kontribusinya. Ã‚Â Populasi Ã‚Â dalamÃ‚Â penelitian Ã‚Â ini Ã‚Â adalah Ã‚Â 85 Ã‚Â orang Ã‚Â siswa Ã‚Â kelas Ã‚Â I Ã‚Â program Ã‚Â keahlian Ã‚Â teknik Ã‚Â mekanik Ã‚Â otomotif. Ã‚Â Pengambilan Ã‚Â sampelÃ‚Â sebanyak Ã‚Â 62 Ã‚Â orang Ã‚Â siswa Ã‚Â menggunakan Ã‚Â Normogram Ã‚Â Harry Ã‚Â King Ã‚Â dengan Ã‚Â teknik Ã‚Â random Ã‚Â sampling. Ã‚Â MetodeÃ‚Â pengumpulan Ã‚Â data menggunakan Ã‚Â dokumentasi, Ã‚Â observasi Ã‚Â dan Ã‚Â tes. Ã‚Â Hasil Ã‚Â penelitian menunjukkan Ã‚Â ada Ã‚Â pengaruhÃ‚Â antara sarana dan prasarana belajar terhadap hasil belajar sebesar 0,6886 (kuat). Hasil penelitian juga menunjukanÃ‚Â kondisi Ã‚Â sarana Ã‚Â dan Ã‚Â prasarana Ã‚Â praktik Ã‚Â belajar Ã‚Â sebesar Ã‚Â 71,83% Ã‚Â dalam Ã‚Â kategori Ã‚Â baik, maka Ã‚Â prestasi Ã‚Â belajar Ã‚Â siswaÃ‚Â dalam alat ukur Ã‚Â linier yang diperoleh masuk dalam kategori baik. Besaran kontribusi pengaruh yang terjadi padaÃ‚Â sarana dan prasarana praktik terhadap hasil belajar alat ukur liner adalah 47,42%.Kata kunci: Sarana, prasarana, praktikum, alat ukurÃ‚Â The Ã‚Â problem Ã‚Â containing Ã‚Â in Ã‚Â this Ã‚Â research Ã‚Â is Ã‚Â how Ã‚Â much Ã‚Â the Ã‚Â effect Ã‚Â of Ã‚Â study Ã‚Â practice Ã‚Â facilities Ã‚Â andÃ‚Â infrastructures Ã‚Â toward Ã‚Â study Ã‚Â result Ã‚Â in Ã‚Â measuring Ã‚Â tool Ã‚Â training Ã‚Â subject Ã‚Â is, Ã‚Â and Ã‚Â how Ã‚Â much Ã‚Â the Ã‚Â contributionÃ‚Â magnitude Ã‚Â is. The population of Ã‚Â the research was about 85 Ã‚Â first graders of automotive mechanical skill program.Ã‚Â The sample of it was approximately 62 students using Normogram Harry King with random sampling Ã‚Â technique.Ã‚Â Data was collected using methods such as documentation, observation, and test. Research result shows that studyÃ‚Â facilities and infrastructures brings around 0,6886 toward study result (strong). Other result is that study facilitiesÃ‚Â and infrastructures are 71,83% in good category. Hence, studentsÃ¢â‚¬â„¢ study achievements using linier measuring toolÃ‚Â are also in good category. The magnitude of effect happening in practice facilities and infrastructures toward studyÃ‚Â result using linier measuring tool is about 47,42%.Keywords: facilities, infrastructures, practice, measuring tool